Novel Porous Boron Nitride Nanosheet with Carbon Doping: Potential Metal‐Free Photocatalyst for Visible‐Light‐Driven Overall Water Splitting. Issue 4 (4th January 2019) - Wan, Qiang; Wei, Fenfei; Ma, Zuju; Anpo, Masakazu; Lin, Sen
Abstract: The band gap of hexagonal boron nitride ( h ‐BN) is far too wide for efficiently utilizing visible light, limiting its application in photocatalysis. The present study employs first principles calculations to demonstrate that the band gap energies of porous h ‐BN ( p ‐BN) can be tuned by carbon doping to levels appropriate for the absorption of visible‐light, and that the conduction band and valence band match well with the potentials of both hydrogen and oxygen evolution reactions. Importantly, a strategy of carbon doping to improve the energy level of valence band maximum is also proposed. Moreover, the carbon‐doped p ‐BN exhibits good separation between photogenerated electrons/holes and structural stability at high temperatures. The DFT results help the design of high‐performance two‐dimensional photocatalysts that avoid the use of metals. Abstract : A novel porous h ‐BN material ( p ‐BN) with carbon doping is demonstrated as a metal‐free 2D photocatalyst for visible‐light‐driven overall water splitting. Importantly, the valence band maximum of p ‐BN can be successfully tuned by carbon doping to locate at energetically favorable level for oxygen evolution reaction. This work helps the design of promising 2D photocatalysts that avoid the use of metals.